Progesterone for smoking relapse prevention following delivery: A pilot, randomized, double-blind study. (December 2017) - Forray, Ariadna; Gilstad-Hayden, Kathryn; Suppies, Cristine; Bogen, Debra; Sofuoglu, Mehmet; Yonkers, Kimberly A.
Highlights: Female smokers frequently quit smoking in pregnancy when progesterone levels are high. Relapse postpartum is common when progesterone levels drop. Progesterone replacement in postpartum women decreased craving for cigarettes. Progesterone showed a trend toward increased abstinence and slower relapse. Findings support the promise of progesterone treatment in postpartum smokers. Abstract: Introduction: Close to half of women who were smokers prior to conception quit smoking in pregnancy, when endogenous progesterone levels are high. However, at least half resume pre-pregnancy smoking levels within weeks after delivery and when progesterone levels drop. The current pilot study tested the feasibility and preliminary efficacy of postpartum progesterone replacement in preventing relapse to smoking in postpartum women with a history of pre-pregnancy smoking. Methods: This was an 8-week, double-blind, parallel, randomized, placebo-controlled pilot trial of 41 women with a history of pre-pregnancy smoking who achieved abstinence by 32 weeks of gestation. Immediately following delivery women were randomized to oral micronized progesterone (200 mg twice daily) or placebo via computerized urn randomization program. The main outcome measures were descriptions of study feasibility: recruitment and retention. Secondary outcomes were 7-day point prevalence of abstinence at week 8, time to relapse and smoking cravings. Results: The trial was feasible with adequate randomization, 64% (41/64) of eligible women, and trial retention, 78% (32/41) completed the trial. Women taking progesterone were 1.8 times more likely to be abstinent during week 8 and took longer to relapse (10 vs. 4 weeks) compared to the placebo group, although these differences did not reach statistical significance. After adjusting for age and pre-quit smoking level, the number needed to treat was 7. There was a 10% greater decline per week in craving ratings in the progesterone group compared to placebo (β = −0.10, 95% CI: −0.15, −0.04, p < 0.01). No serious adverse events occurred during the trial. Conclusions: These preliminary findings support the promise of progesterone treatment in postpartum smokers and could constitute a therapeutic breakthrough.If these preliminary findings can be evaluated and replicated in a larger study with sufficient power, this may constitute an acceptable and safe smoking relapse prevention strategy for use during lactation.